Observed changes in Brewer–Dobson circulation for 1980–2018. (8th November 2019) - Fu, Qiang; Solomon, Susan; Pahlavan, Hamid A; Lin, Pu
Abstract: Previous work has examined the Brewer–Dobson circulation (BDC) changes for 1980–2009 based on satellite Microwave Sounding Unit (MSU/AMSU) lower-stratospheric temperature ( T LS ) observations and ERA-Interim reanalysis data. Here we examine the BDC changes for the longer period now available (1980–2018), which also allows analysis of both the ozone depletion (1980–1999) and ozone healing (2000–2018) periods. We provide observational evidence that the annual mean BDC accelerated for 1980–1999 but decelerated for 2000–2018, with the changes largely driven by the Southern Hemisphere (SH), which might be partly contributed by the effects of ozone depletion and healing. We also show that the annual mean BDC has accelerated in the last 40 years (at the 90% confidence level) with a relative strengthening of ∼1.7% per decade. This overall acceleration was driven by both Northern Hemisphere (40%) and SH (60%) cells. Significant SH radiative warming is also identified in September for 2000–2018 after excluding the year 2002 when a very rare SH stratospheric sudden warming occurred, supporting the view that healing of the Antarctic ozone layer has now begun to occur during the month of September.